Biomimic pH/reduction dual-sensitive reversibly cross-linked hyaluronic acid prodrug micelles for targeted intracellular drug delivery. (12th October 2015) - Wang, Lin; Wang, Yin; Jin, Qiao; Jia, Fan; Wang, Haibo; Ji, Jian
Abstract: Biomimic hyaluronic acid (HA) prodrug micelles with pH and reduction responsiveness were prepared by chemical graft of phosphorylcholine and doxorubicin (DOX) to the backbone of HA. DOX was conjugated to HA by pH-sensitive hydrazone bonds which could be hydrolyzed under acidic conditions and thus resulted in controlled release of DOX. Besides, the HA prodrug micelles were cross-linked via reduction-responsive disulfide bonds to improve the stability of the micelles. The HA prodrug can form remarkable core–shell micelles with a quite narrow size distribution which was confirmed by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The in vitro drug release studies showed that there was a dramatic release under endosome pH (pH = 5.0) and reductive environment (10 mM of dithiothreitol) than that at normal physiological environment (pH = 7.4). Greater uptake of DOX from HA prodrug micelles was observed in the CD44 receptor highly expressed MDA-MB-231 cell line, compared to the results from the CD44-negative cell line, NIH3T3, which was demonstrated by the flow cytometry and ﬂuorescence microscopy. The glutathione (GSH)-responsive behaviors were studied as well. The micelles showed higher cellular proliferation inhibition against glutathione monoester (GSH-OEt) pretreated MDA-MB-231 cells than that of the non-pretreated and buthionine sulfoximine (BSO) pretreated ones. These results suggested that such pH/reduction dual-responsive prodrug micelles may enhance the selective inhibition to cancer cells which exhibit higher levels of GSH concentration and provide favorable platforms for cancer therapy. Graphical abstract: Highlights: Hyaluronic acid prodrugs with pH and reduction responsiveness were prepared. The prodrug can form remarkable micelles with a narrow size distribution. The micelles could accumulate at the tumor site actively. The prodrug system can inhibit the proliferation of the cancer cells effectively.